A FAIR PRICE PRINCIPLE IN SQUEEZE-OUT ACQUISITIONS - Jinoria, Khatuna (European Scientific Journal, ESJ, 2015)
Fair price is the important criterion in squeeze-out acquisitions. Entrepreneur’s law of Georgia unites mandatory tender offer and mandatory acquisition of shares under this hood. Both institutions are examples of compulsory contracting and with their essence are interruptions into shareholders property rights. In those cases, redemption is almost only measure offered to minority shareholders, which is exactly why it is vital to ensure, that shareholders receive adequate compensation for the unwilling disposal of their property.